Using Crossword Puzzle to increase Students’ Vocabularies for Writing Skill in Descriptive Text - Rusmawan, Putu Ngurah (Institut Agama Islam Negeri (IAIN) Curup, 2018)
The purpose of the study is to know using media puzzle improve the students writing descriptive text for the second graders at SMP Negeri 5 Pasuruan. The researcher used a classroom action research. This research was conducted on April 05th 2017 to May 06th 2017. To get the information about the implementation of the crossword puzzle in descriptive text for writing skill, the researcher used interview, observation, questionnaire, test and documentation. The result of the test at the end of the first cycle showed that 26 students got under 76. It was not successful because it was still below criteria of success which required at least 76 as minimum score. In the cycle two, there were 27 students who got at least or more 76. It can be concluded that all students got the criteria of success, which required at least 76 as the minimum score. Finally, it can be concluded that the result of this research showed that using crossword puzzle can improve the students’ writing skill in teaching learning English. It can help the students to memorize the material easily and it can give positive effect for the students Keywords: Writing, Descriptive, Crossword Puzzle.